PENGARUH GADAI AGUNAN BUKU PEMILIK KENDARAAN BERMOTOR (BPKB) TERHADAP PENGEMBANGAN USAHA KECIL DAN MENENGAH (UKM - Risna Risna; M. Zakariah; Sulman Sulman (Jurnal Ekonomi Bisnis Syariah, 2020)
The problem of this research is that business growth in society is getting higher but these entrepreneurs or entrepreneurs lack the capital to develop their business.The formulation of the problem in this study is whether there is an effect of BPKB collateral pawning on the development of small and medium enterprises (UKM) at PT. Pegadaian Kolaka. The purpose of this study was to analyze whether the BPKB collateral pawning could affect the development of small and medium enterprises (UKM).The research method used includes quantitative research types, using purposive sampling technique. The population is the customers of PT. Pegadaian Kolaka that took BPKB collateral pawning products, namely KREASI Products, totaling 107 customers. For the dependent variable (Y), namely the development of small and medium enterprises (UKM), for the independent variable (X). Collecting data using a questionnaire and analyzed using a simple regression test.The results of this study are that there is a significant effect between BPKB pawning on the development of SMEs, the percentage yield is 66.4%, while the difference from the percentage means it is owned by other factors